Program Kehamilan - Abaraham (Conferences of Medical Sciences Dies Natalis, 2019)
In 2016, at the beginning of Sustainable Development Goals (SDGs) era, preventable morbidity and mortality rates related to pregnancy remained very high. In the series of reproductive health care, antenatal care (ANC) facilitates important health service functions, including health promotion, premarital and preconception screening, diagnosis, and prevention of disease. Antenatal care in nulliparous women without complications was performed up to 10 times, while in primiparous and multiparous women without complications of pregnancy, ANC examination is recommended to be performed 7 times during the pregnancy period. Premarital screening is an action to prevent health problems in yourself, your spouse or offspring. This examination has several advantages, namely to prevent various diseases in the babies, such as thalassemia, diabetes mellitus, and other diseases. Preconception care aims to prevent and control disease at various stages of life, and a strong public health program is needed which uses a life perspective from infancy through childhood, adolescence and adulthood. Preconception care packages along with evidence-based interventions suggested by the World Health Organization include nutritional conditions; tobacco use; genetic conditions; environmental health; use of vaccines; prevention of interpersonal violence, sexually transmitted infections, drugs use, and Female Genital Mutilation (FGM).